2004
DOI: 10.1111/j.1365-3032.2004.00374.x
|View full text |Cite
|
Sign up to set email alerts
|

Food‐dependent regurgitate effectiveness in the defence of grasshoppers against ants: the case of bracken‐fed Abracris flavolineata (Orthoptera: Acrididae)

Abstract: The deterrence of a grasshopper, Abracris flavolineata, regurgitate against the fire ant, Solenopsis geminata, depends on diet. The ant deterrence of oral discharges of bracken-fed insects is greater than for those feeding on lettuce. A water extract of Pteridium caudatum fronds is also more potent in deterring the ants than a lettuce extract. A positive correlation between the content of phenolics in the regurgitate and deterrence is observed and bracken-derived oral fluids contain a 4.6-fold higher content o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…Therefore, we expected to find a tritrophic effect of plant secondary compounds, from plant to insects and then to rollers. In agreement with our expectation, we found that all vomit samples contained hydroxycinnamic and hydroxybenzoic acids, that are phenolic acids usually found in leaves of many Gramineae and cell walls of most higher plants [18], [28], [41] and that deter insect feeding [29], [42]. Furthermore, some samples also contained traces of psoralen that is a furacoumarin produced by a wide variety of plants in response to pathogens and/or herbivore attacks [17].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, we expected to find a tritrophic effect of plant secondary compounds, from plant to insects and then to rollers. In agreement with our expectation, we found that all vomit samples contained hydroxycinnamic and hydroxybenzoic acids, that are phenolic acids usually found in leaves of many Gramineae and cell walls of most higher plants [18], [28], [41] and that deter insect feeding [29], [42]. Furthermore, some samples also contained traces of psoralen that is a furacoumarin produced by a wide variety of plants in response to pathogens and/or herbivore attacks [17].…”
Section: Discussionsupporting
confidence: 90%
“…These armed insects, hunted by adult rollers to feed their offspring, would be the putative source of phenolic acids contained in the vomit of roller. Previous work has demonstrated that oral secretion of different grasshopper species can deter predators [16][18], [31]. Here, for the first time, we show the deterrent effect of the oral secretion of a vertebrate, the avoidance of the oral secretion of nestling rollers by domestic dogs.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Additionally, they may also be an important part of chemical defense, because grasshoppers regurgitate copious amounts of frothy secretions as a defense against attack. Indeed, investigations (36)(37)(38) have shown that both compounds from host plants and insect produced water-soluble components of the regurgitant have deterrent activity (36). Although the deterrent effect of caeliferins remains to be tested, it is probable that the emulsifying properties are important in aiding the water-based regurgitant to carry lipophillic toxic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Enteric discharges from herbivores contain recently consumed plant material mixed with digestive and salivary secretions (Ortego et al 1997), but their mode of defence has been attributed primarily to ingested plant secondary compounds (e.g. Sword 2001;Calcagno et al 2004). Thus, defence seems to depend strongly on a herbivore's food plant.…”
Section: Introductionmentioning
confidence: 99%